Factoring Central Asia in the Russia-India Energy Trade - A. Dhaka; M. Dmitrieva (Vestnik MGIMO-Universiteta, 2020)
The article looks into the Russia-India energy trade potential and its strategic significance with a particular focus on the Central Asian energy trade. Russia has become a major player in the energy market and its handling of Syrian crisis has enhanced its position in the Middle East that has impact on oil market and production scenario. India has been a growing at a rate of above 5% and its energy needs have been substantial. India and Russia share a very special relationship due to long-standing cultural and political ties and this has been a facilitator to India’s energy security needs. The Central Asian Republics hold a special position for Russia and India in terms of strategic security across South and Central Asian region. The two countries not only deeply connect themselves with the region but also find it necessary to preserve the region from religious extremism and terrorism that is worsened by the narcotics and arms trade. The Central Asian republics are a house to some of the world’s largest natural gas reserves and they have been exporting it large volumes through pipelines. However, the approach has not materialised as South Asia due to the Afghanistan situation. Therefore, Russia remains an important route to access energy resources from Eurasia and Central Asia in particular. India also has high exposure to the maritime energy trade with Africa and Latin America countries that contribute to the counting opportunity cost for accessing Central Asian energy. The paper highlights the significance of energy trade between Russia, India and Central Asian countries that could contribute to geopolitical stability across the region.